A wellbeing economy focused on planetary health should be top of the COP27 agenda. (12th October 2022) - Buse, Kent; Hunnisett, Chelsea; Pillay, Yogan
Abstract : Delegations converging in Egypt for the Conference of the Parties must set their sights on a fundamental economic reset with planetary health at its core, argue Kent Buse and colleagues